2021
DOI: 10.1055/a-1698-8469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Oregano (Lippia origanoides) and Clover (Eugenia caryophillata) Essential Oilsʼ Formulations on Intestinal Health and Performance of Pigs

Abstract: The incorporation of natural essential oils to the pigsʼ diet in intensive production systems is a potential tool to improve gut health and prevent infections without using antibiotics. Nevertheless, different products, even containing the same compounds, coming from the same botanical species, may exert dissimilar biological effects due differences in the technological processes by which they are produced and preserved. For this reason, suitability of a given product based on natural extracts, intended for sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
2
0
1
Order By: Relevance
“…In previous studies, we obtained similar citrullinemia profiles in weaned piglets that received different diets. 29 These events are consistent with Montagne et al, 10 who described detrimental changes in the gut architecture and function associated to weaning during an acute and short time period (up to 5 days postweaning) followed by a gradual adaptative and maturational phase. Also, in agreement with our findings, Berkeveld et al 8 showed that weaned piglets had lower plasmatic citrulline concentrations than their unweaned littermates during the first week postweaning with the nadir 4 days postweaning.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In previous studies, we obtained similar citrullinemia profiles in weaned piglets that received different diets. 29 These events are consistent with Montagne et al, 10 who described detrimental changes in the gut architecture and function associated to weaning during an acute and short time period (up to 5 days postweaning) followed by a gradual adaptative and maturational phase. Also, in agreement with our findings, Berkeveld et al 8 showed that weaned piglets had lower plasmatic citrulline concentrations than their unweaned littermates during the first week postweaning with the nadir 4 days postweaning.…”
Section: Discussionsupporting
confidence: 91%
“…The cortisol surge that we observed during the initiation of the postweaning period in the present study is in agreement with other investigations. 29,36,37 Noteworthy, even though Wu et al 37 demonstrated that augmented cortisol levels after weaning enhance the transcription of pyrroline-5-carboxylate synthase mRNA and therefore the capacity of enterocytes for citrulline synthesis from glutamine, it is possible that the lack of substrates overrides the improved enzymatic activity. The upregulation of citrulline biosynthetic pathway by cortisol may be an adaptative response to the lack of nutrient absorption during stressful situations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the CON group, CEO supplementation in this study enhanced VH, CD, and the VH:CD ratio in nursery pigs. SN Dieguez, JM Decundo, G Martínez, FA Amanto, CP Bianchi, DS Pérez Gaudio and AL Soraci [ 25 ] demonstrated that dietary supplemented oregano essential oil improved intestinal architecture. Given that the total luminal villus’ absorptive surface area and the VH:CD ratio have a positive correlation [ 26 ], our results suggest suggested that EO treatment can increase the absorption surface area and increase the utilization rate of feed.…”
Section: Discussionmentioning
confidence: 99%
“…Оскільки ефірні олії є ліпофільними та леткими, є проблема ефективного потрапляння ефірних олій у кишечник свині, і цю проблему можна частково вирішити за допомогою мікрокапсуляції та нанотехнологій. Нещодавно були розроблені технології високопродуктивних систем, які дозволяють нам вивчити механізми, що ле-жать в основі функції ефірних олій і полегшить їх використання у свинарстві (Reichling et al, 2009;Vaillancourt et al, 2018;Omonijo et al, 2018;Ruzauskas et al, 2020;Peng et al, 2021;Dieguez et al, 2022).…”
Section: вступunclassified